Persistence and effect of decontamination processes on reduction of cypermethrin in okra (Abelmoschus esculentus) fruits - CHAUHAN, REENA; SINGH, DHARMENDAR; MONGA, SAMRITI; KUMARI, BEENA (The Indian Journal of Agricultural Sciences, 2018)
Persistence of cypermethrin and decontamination processes on reduction of cypermethrin residues was studied in okra (Abelmoschus esculentus L.) fruits following foliar application of formulation at dose of 50 and 100 g a. i./ha in a field at the Research field of CCS HAU, Hisar, India. Samples of okra fruits were collected periodically and residues were estimated by GC-ECD and confirmed by GC-MS. The average initial deposits of cypermethrin were 0.119 and 0.272 mg/kg in the okra fruits at single and double dose, respectively, one hour after the application. Residues of cypermethrin reached equal to below determination level (0.01mg/kg) on 10th in single dose and after 15 days at double dose. Half-life periods for cypermethrin were observed to be 2.74 days and 3.31 days at single and double dose, respectively following first order kinetics. Residues were below maximum residue limit (MRL) value of 0.2 mg/kg on 0 day in single dose and 1 day in double dose. Safe waiting period of 2 days has been suggested for safety sake. Decontamination processes were found very effective in reducing the residues of cypermethrin in okra fruits. Washing reduced the residues in the range of 39-41 %, whereas washing followed by boiling reduced 71 to 79% residues. In soil, residues of cypermethrin reached below detectable level of 0.005 mg/kg after 3rd and 5th days of application at single and double dose, respectively.